Analysis of Service Performance in The Domestic and Civil Department of Bone Bolango Regency, Gorontalo Province - Yanti Aneta; Aisya Jassin (Journal of International Conference Proceedings (JICP), 2019)
This study aims to analyze the performance of services in the population and civil registration offices of Bone Bolango District, and the determinants in improving service performance in the Population and Civil Registry Kabuoaten Bone Bolango. This type of research is qualitative research with a case study approach. Data collection is done through interviews, observation and documentation. Technical data analysis is used through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that (1) the performance of the state civil service apratur in the Population and Civil Registry Service of Bone Bolango Regency is applied in accordance with the principles of public service principles that cover 10 (ten Aspects), where only 2 (two) aspects have gone well, namely aspects ease of access, and aspects. Meanwhile 8 (eight) aspects consisting of aspects of simplicity, clarity, certainty of time, accuracy, security, responsibility, and completeness of facilities and infrastructure have not been implemented properly so that it is still needed to be addressed and improved the service process. (2) The factors that determine the improvement of the performance of human resources services are; a) Human Performance Perspective, namely the motivation and ability factors of the apparatus that are still lacking in supporting the service implementation process so that performance achievements are not optimal, b) Organizational Perspective, that is communication factors that have not been effective cause information that is not managed and utilized optimally.